The legality of colonial domination in southeastern Australia (2010)
This article intends to shed new light on the patterns of the law's fabric in colonial contexts. It is based on two legal discussions concerning the nature of the relationships between the police and the indigenous population in rural New South Wales (NSW) after the Second World War. The first casestudy deals with the justification of the special powers which the police officers enjoyed in the reserves and stations of the Aboriginal Welfare Board. The second case-study revolves around the Aboriginals' prohibition from consuming alcohol. I will describe in detail a trial which ended unexpectedly in 1961, provoking a complete reassessment of police practices in their dealing with infringements of the Aboriginal Protection Act (APA).